Histological characteristics and markers of proliferation and differentiation in rat brain with experimental glioma - Ristić, Slavica; Mirić, Mirjana; Jović, Sladjana; Ristić, Siniša; Karić, Jasmina (Vojnosanitetski pregled, 2014)
Background/Aim. The cell line C6 is a continuous cell line of rat glioma and, as a transplantable line, is frequently used for induction into in vivo model of primary brain tumor. It is believed that, pursuant to its histological traits and biological behavior, this experimental tumor corresponds to human anaplastic astrocytoma of grade II/III, which is characterized by proliferative and invasive potency, and marked cell differentiation. The aim of this study was to determine macroscopic analysis of rat brain with implanted tumor during tumorigenesis, histological features of tumor cells of induced brain tumor and markers of proliferation (proliferation cell nuclear antigen – PCNA, cytokeratin – CK 19) and differentiation (glial fibrillary acidic protein – GFAP) in rat brain with implanted tumor. Methods. To determine histological structure of the brain with implanted C6 cells, we used brain sections stained for hematoxylin-eosin or kresyl violet, whereas other sections were immunohistochemically stained for GFAP, CK 19 and PCNA. Results. A statistically significant difference in weights of the left and right brain hemispheres with implanted tumors during tumorigenesis in as soon as 7 days from the day of inducing tumors was revealed. The tumor was of cellular type, with distinct pleomorphism of cells and frequent hyperchromasia of the nucleus. Immunohistochemical staining for PCNA revealed a significant number of positive cells on the days 7, 14 and 21 day following the implantation of C6 cells. CK 19 positive cells were present in both brain hemispheres, and numerous GFAP positive astrocytes were found around the puncture lesion. Conclusions. Within the experimental conditions of the present research, C6 glioma did not demonstrate any relevant deviations concerning development, clinical symptomatology and macroscopic anatomy relative to those already described in the literature.
Keywords: glioma; rats; disease models; animal; immunohistochemistry